The governor's wife - Harvey, Michael T. (Harvey, Michael T. Michael Kelly mysteries., 2015)
Receiving a lucrative anonymous offer to track down an escaped criminal, private investigator Michael Kelly unwinds the past of the fugitive's wife, who harbors deeply complicated and dangerous reasons for standing by her husband.